Proposta de metodologia de apoio ao controle interno baseada na distribuição de Newcomb-Benford para análise de contratos públicos - Freitas, Sonia Maria de (2019)
This paper proposed a methodology based on the Newcomb-Benford Distribution, or Benford Distribution, to be used by government agency internal control systems to analyze the quantities of public works contract spreadsheets. The Newcomb-Benford Distribution is considered an anomaly of probabilities and indicates that the frequency of the first digits in a set of numbers in a real database is decreasing, that is, the probability of occurrence of number 1 is higher than the others. numbers and so on. Based on the comparison between the observed frequencies and those predicted in the Distribution, it is possible to select samples that present greater relevance in terms of representativeness of values, as well as the possibility of data manipulation. The theoretical basis included the Newcomb-Benford Distribution and its applications, the constitutional obligation of the institution of internal control systems and their attributions, the methodologies used by control systems in the analysis of budget spreadsheets. For the study we developed an algorithm based on Benford Distribution, in free platform, which was tested in the contract spreadsheets quantitative of a body responsible for the transport infrastructure acting in all Brazilian states, including Paraná. The results indicate the possibility of using the methodology in the process of selection of auditable process samples in order to search for possible anomalies in public works contracts, even anticipating possible questioning by an external control.